Optimising alkalinisation and its effect on QRS narrowing in tricyclic antidepressant poisoning. Issue 2 (31st August 2021) - Pai, Kieran; Buckley, Nicholas A.; Isoardi, Katherine Z.; Isbister, Geoffrey K.; Becker, Therese; Chiew, Angela L.; Cairns, Rose; Brown, Jared A.; Chan, Betty S.
Abstract : Aims: The objectives were to determine the effect of NaHCO3 and/or mechanical ventilation on the biochemical profile and serum alkalinisation in tricyclic antidepressant (TCA) poisoning and investigate the impact of effective alkalinisation therapy on the QRS interval in TCA poisoning. Methods: This was a retrospective review of TCA poisonings from three Australian toxicology units and a poisons information centre (Jan 2013 to Jan 2019). We included patients with TCA toxicity who ingested>10 mg/kg or had clinically significant toxicities consistent with TCA poisoning, and analysed patients' clinical, electrocardiogram and biochemical data. Results: Of 210 patients, 84 received NaHCO3 and ventilation (dual therapy), 12 NaHCO3, 46 ventilation and 68 supportive care treatment. When compared with single/supportive groups, patients who received dual therapy had taken a significantly higher median dose of TCA (1.5 g vs 1.3 g, P  < .001), a longer median maximum QRS interval (124 ms, interquartile ranges [IQR] 108‐138 vs 106 ms, IQR 98‐115, P  < .001) and were more likely to have seizures (14% vs 3%, P  = .006) and arrhythmias (17% vs 1%, P  < .001). The dual therapy group demonstrated greater increases in serum pH (median 0.11, IQR 0.04‐0.17) compared to the single/supportive therapy group (median 0.03, IQR −0.01‐0.09, p  < .001). A greater proportion of patients reached the target pH 7.45‐7.55 in the dual therapy group (59%) compared to the single/supportive therapy group (10%) ( P  < .001). For each 100 mmol bolus of NaHCO3 given, the median increase in serum sodium was 2.5 mmol/L (IQR 1.5‐4.0). QRS narrowing occurred twice as quickly in the dual therapy vs single/supportive therapy group. Conclusions: A combination of NaHCO3 and mechanical ventilation was most effective in achieving serum alkalinisation and was associated with a more rapid narrowing of the QRS interval. We advise that the maximal dose of NaHCO3 should be <400 mmol (6 mmol/kg). Abstract :